Competitive Advantage Theory Vs. Practice: Examination Of Management Mindset A Study In Malaysia - Ghamari, Jamal (2009)
This study intends to conceptualize competitive advantage along the five mentioned aspects and then deliberately delve into managers' mental models regarding those aspects.